'Court'ing Hindu nationalism: law and the rise of modern Hindutva*. Issue 4 (2nd October 2018) - Saxena, Saumya
ABSTRACT: This paper demonstrates the role of the Courts in lending currency to the politics of Hindutva in the 1990s. It focuses on some of the significant and connected cases of the Ayodhya dispute and the infamous Hindutva judgments to illustrate how the court legitimised, perhaps inadvertently, a jingoistic and intolerant ideology as an acceptable political strategy. The rise and electoral successes of the Bharatiya Janata Party (BJP) post-emergency accompanied the party's reliance on the judicial instruments to make its Hindu nationalist ideology palatable to a larger audience and the 'secular' citizen. Contrary to the stance of Hindu nationalist organisations against codification of Hindu law and any state interference in matters of religion at the time of independence, in the 1990s the movement relied significantly on judicial instruments for its own legitimacy and for expanding the domain of religion by seeking the patronage of 'law'. The Court, in what came to be known as the Hindutva judgments, attempted to separate 'Hindutva' from 'Hinduism', thereby aiding the launch of a new dawn of Hindutva which could then become synonymous with democracy and development. Most significantly, it also opened the doors for electoral promises to be routed through the courts.